Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

7 (a+1)-3a=5+4 (2a-1)

Sagot :

Use the distributive property

7(a)+7(1)-3a = 5+4(2a)+4(-1)

Multiply and then add to get your final answer.
[tex]7(a+1)-3a=5+4(2a-1) \\ \\ 7a+7-3a=5+8a-4 \\ \\ 4a+7=8a+1 \\ \\ 4a-8a=1-7 \\ \\ -4a=-6 \\ \\ \boxed{a=\frac{-6}{-4}= \frac{3}{2}}[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.